The Impact Of Strategic Vigilance On Strategic Success: An Analytical Study Of The Opinions Of A Sample Of Lecturers At Samarra University - Mohammed Ahmed Mhmood (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The current research aims to measure the impact of strategic vigilance through its dimensions (strategic vigilance, competitive vigilance, technological vigilance, environmental vigilance) on strategic success in its dimensions (survival, growth, adaptation), and the problem of the study is defined in the following question: What is the role of strategic vigilance in achieving strategic success? The aim of the study came to identify the role that strategic vigilance can play in achieving strategic success. The questionnaire form was distributed to a sample of lecturers at Samarra University, with a strength of (88) lecturers. The research used a descriptive analytical approach, which was followed by statistical methods like arithmetic mean, standard deviation, linear correlation coefficient, simple and multiple regression coefficient, and statistical programs like SPSS.V.29 and Amos.V.26 to analyze the data and draw conclusions. The most notable of these claims was that strategic vigilance influences strategic success.